How Does a Delay Between Temperate Running Exercise and Hot-Water Immersion Alter the Acute Thermoregulatory Response and Heat-Load? - Heathcote, Storme L.; Hassmén, Peter; Zhou, Shi; Taylor, Lee; Stevens, Christopher J. (Frontiers in Physiology, 2019)
Hot-water immersion following exercise in a temperate environment can elicit heat acclimation in endurance-trained individuals. However, a delay between exercise cessation and immersion is likely a common occurrence in practice. Precisely how such a delay potentially alters hot-water immersion mediated acute physiological responses (e.g. total heat-load) remains unexplored. Such data would aid in optimising prescription of post-exercise hot-water immersion in cool environments, relative to heat acclimation goals. Twelve male recreational runners (mean ± SD; age: 38 ± 13 y, height: 180 ± 7 cm, body mass: 81 ± 13.7 kg, body fat: 13.9 ± 3.5%) completed three separate 40-minute treadmill runs (18°C), followed by either a 10 min (10M), 1 h (1H) or 8 h (8H) delay, prior to a 30-minute hot-water immersion (39°C), with a randomised crossover design. Core and skin temperatures, heart rate, sweat and perceptual responses were measured across the trials. Mean core temperature during immersion was significantly lower in 1H (37.39 ± 0.30°C) compared to 10M (37.83 ± 0.24°C; P = 0.0032) and 8H (37.74 ± 0.19°C; P = 0.0140). Mean skin temperature was significantly higher in 8H (32.70 ± 0.41°C) compared to 10M (31.93 ± 0.60°C; P = 0.0042) at the end of the hot-water immersion. Mean and maximal heart rates were also higher during immersion in 10M compared to 1H and 8H (P < 0.05), despite no significant differences in the sweat or perceptual responses. The shortest delay between exercise and immersion (10M) provoked the greatest heat-load during immersion. However, performing the hot-water immersion in the afternoon (8H), which coincided with peak circadian body temperature, provided a larger heat-load stimulus than the 1 h delay (1H).